1998
DOI: 10.1111/j.1365-2621.1998.tb15838.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Starch Interactions as Evidenced by Viscosity and Dielectric Property Measurements

Abstract: Increasing the concentration of salt (NaCl) or starch in a saltstarch solution depressed the dielectric constant and loss factor relative to a pure salt solution, except for the loss factor when no salt was present. The addition of salt to a starch solution increased the viscosity. Both viscosity and dielectric properties were decreased by mechanical agitation and by action of amylase. Above 10% starch the decrease in dielectric loss was abrupt, corresponding to the increase in viscosity. The changes were hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 11 publications
5
39
1
Order By: Relevance
“…As salt and sugar are the most important ingredients usually used in food industry, the physicochemical properties of starch-based food often change by addition of salt and sugar during food processing and storage. Viscosity of corn starch could be increased with salt 2 . Peak viscosity of cassava starch could be promoted with 2.5-5% NaCl 3 .…”
Section: Introductionmentioning
confidence: 91%
“…As salt and sugar are the most important ingredients usually used in food industry, the physicochemical properties of starch-based food often change by addition of salt and sugar during food processing and storage. Viscosity of corn starch could be increased with salt 2 . Peak viscosity of cassava starch could be promoted with 2.5-5% NaCl 3 .…”
Section: Introductionmentioning
confidence: 91%
“…At this concentration, the reduced breakdown could be traced to the corresponding low peak viscosity. The higher breakdown in the case of alum and aluminium chloride brings about disruption of starch granules [10]. Thus, sodium chloride, sodium sulphite and sodium thiosulphate stabilised the starch pastes, while ferrous sulphate, aluminium chloride and alum caused a decrease in paste stability.…”
Section: Effect On Breakdown In Viscositymentioning
confidence: 98%
“…It has been observed that sodium thiosulphate at some definite concentrations, lowered the swelling volumes to very low values, but the Brabender viscosity was not affected at the same concentrations [5]. At higher concentrations and continuous stirring the ORD may not be prominent and hence there was no effect on viscosity [4,10]. Moore et al reported that addition of calcium chloride brings about lowering of viscosity of potato starch.…”
Section: Effect Of Salts On Peak Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Adding salt to food systems with a high water content is known to increase the e 00 . Bircan and Barringer (1998) observed that adding salt to water caused a greater increase in the loss factor than that for pure water. reported a significant increase in the loss factor in corn starch solutions when the concentration of salt increased (measured at different frequencies and temperatures); this increase was attributed to the higher conductivity of salt.…”
Section: Dielectric Propertiesmentioning
confidence: 88%